Sphingosine-1-Phosphate (S-1P) Promotes Differentiation of Naive Macrophages and Enhances Protective Immunity Against Mycobacterium tuberculosis - Nadella, Vinod; Sharma, Lalita; Kumar, Pankaj; Gupta, Pushpa; Gupta, Umesh D.; Tripathi, Srikant; Pothani, Suresh; Qadri, S. S. Y. H.; Prakash, Hridayesh (Frontiers in Immunology, 2020)
Sphingosine-1 phosphate (S-1P) is a key sphingolipid and involved in pathobiology of various respiratory diseases. We have previously demonstrated the significance of S-1P in controlling non-pathogenic mycobacterial infection in macrophages and here we demonstrate the therapeutic potential of S-1P against pathogenic Mycobacterium tuberculosis (H37Rv) also in the mouse model of infection. Our study revealed that S-1P is involved in the expression of iNOS proteins in macrophages, their polarization towards M1 phenotype and secretion of IFN- during the course of infection. S-1P is also capable of enhancing infiltration of pulmonary CD11b+ macrophages and expression of S-1P receptors-3 (S-1PR3) in the lungs during the course of infection. We further revealed the influence of S-1P on major signalling components of inflammatory signalling pathways during M. tb infection thus highlighting anti-mycobacterial potential of S-1P in animals. Taken together, our data suggests that boosting S-1P levels by Sphingolipids mimetic compounds / drugs can be used as immune adjuvant for boosting immunity against pathogenic mycobacteria.